Personal social networks of families comprised of deaf parents and their hearing children - Abianna, Maria Carolina (2022)
The demands of deafness and CODA families are historically neglected and thought from the listener perspective. The overload of such families in the face of the precarious help of institutional and community networks is an important challenge to be understood. This paper aimed to describe qualitatively the characteristics of the Personal Social Network of CODA families. Thus, a Personal Social Network instrument was translated, adapted and used. The LIBRAS and Portuguese versions of the instrument were answered by members of 4 CODA families. The data was analyzed with the Personal Social Network theory. Among the results, issues as the guarantee of inclusion being based on solutions from the family itself, precarious support by the community and formal institutions due to the lack of interpreters, resulting in overload of the parent-child subsystem, are highlighted. More studies are suggested, focused on the anthropological understanding of deafness, qualifying effective inclusion actions.